Increased fat and polyunsaturated fatty acid content in sow gestation diet has no effect on gene expression in progeny during the first 7 days of life. Issue 1 (11th May 2015) - de Greeff, A.; Bikker, P.; Smit‐Heinsbroek, A.; Bruininx, E.; Zwolschen, H.; Fijten, H.; Zetteler, P.; Vastenhouw, S.; Smits, M.; Rebel, J.
Summary: The 'developmental origins of health and disease' hypothesis proposes not only that we are what we eat, but also that we could be what our parents ate. Here, we aimed to improve health and performance of young piglets via maternal diets based on the hypothesis that maternal nutritional interventions change metabolic programming in piglets, reflected by differential gene expression early in life. Therefore, sows were fed either a regular diet, based on barley, wheat and wheat by‐products, sugar beet pulp, palm oil and oilseed meal, or a high‐fat (HF) diet consisting of the regular diet supplemented with an additional amount of 3.5% soybean oil and 1% fish oil at the expense of palm oil and wheat. Performance results, physiological parameters and gene expression in liver of piglets and blood of piglets and sows at day 7 after farrowing from both diet groups were compared. The HF diet tended to enhance growth rate of the offspring in the first week of life. No significant differences in gene expression in liver tissue and blood could be detected between the two groups, neither with whole‐genome microarray analysis, nor with gene specific qPCR analysis. In this study, the feeding of a high‐fat diet with increased amounts of polyunsaturated fatty acid (PUFA) to gestating sows under practical farm settings did not induce significant changes in gene expression in sows and offspring.